STEP CHANGE : the leader's journey. - Watkins, Alan (ROUTLEDGE, 2021)
No one likes change. Too often it's viewed as something that must be endured; something to get through' as fast as possible so that everything can return to normal'. We need to change our view of change and see it for the opportunity it really is. Step Change: The Leader's Journey helps leaders to become gifted and skilful at moving through the change process gracefully and productively. Based on Joseph Campbell's 'hero's journey', Step Change: The Leader's Journey offers a universal road map of change from step-1 (comfort zone) through to step-12 (post-delivery inspiration). The journey travels through four distinctphases of discover', decide', develop' and deliver'. Step Change provides a proven formula for change, both personal and organisational, which allows us to know where we are on the Change Wheel andwhat to expect from each step, including what it looks and feels like at each step. By identifying what causes change to fail at each step as well as tools to navigate past the pitfalls and dead ends that leave us stuck at a particular step or retreating to the comfort zone, the change cycle can be understood and mastered. The book provides the ideal structure for senior managers, human resource managers, coaches and business leaders to follow in order to embed change across their teams and organisation.